1991
DOI: 10.1007/bf00395803
|View full text |Cite
|
Sign up to set email alerts
|

Medial approach open reduction for congenital dislocation of the hip using the Ferguson procedure

Abstract: Between January 1979 and October 1984, 31 congenitally dislocated hips in 19 patients were treated using open reduction via the medial approach, as described by Ferguson, at the Ankara University Faculty of Medicine. Patient age at operation ranged from 3 to 33 months (mean 12.1 months). The average follow-up was 94.7 months. All hips were evaluated both radiographically and clinically. Avascular necrosis of the femoral head was observed in 9.7% and slight, transient ischaemic radiographic changes of the femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 13 publications
1
30
1
Order By: Relevance
“…Anterior open reduction has been recommended in children with complete hip dislocation who are older than 24 months [84]. This same recommendation was made by many authors who advocated medial open reduction in children younger than 24 months [11,16,21,40,46,49,50,52,53,77,85,88]. Although we were aware of this general trend in favor of anterior open reduction that provides capsulorrhaphy and avoids medial circumflex vessels, the good preliminary results we obtained in children older than 24 months encouraged us to increase the upper age limit for medial open reduction to 36 months.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Anterior open reduction has been recommended in children with complete hip dislocation who are older than 24 months [84]. This same recommendation was made by many authors who advocated medial open reduction in children younger than 24 months [11,16,21,40,46,49,50,52,53,77,85,88]. Although we were aware of this general trend in favor of anterior open reduction that provides capsulorrhaphy and avoids medial circumflex vessels, the good preliminary results we obtained in children older than 24 months encouraged us to increase the upper age limit for medial open reduction to 36 months.…”
Section: Discussionmentioning
confidence: 92%
“…Although medial versus anterior open reduction is debated with complete dislocations [11,16,21,40,46,49,50,52,53,64,77,84,85,88], open medial reduction after preliminary traction gave us good results. All hips in our patients remained stable after completion of treatment and the acetabular index normalized in all of them.…”
Section: Discussionmentioning
confidence: 99%
“…Mergen et al observed ON only in patients younger than 7 months and older than 18 months [14]. Castillo and Sherman and Mankey et al reported ON correlated positively with increased age at surgery [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Mergen et al reported patients having a medial approach for open reduction and between 7 and 18 months old at the time of surgery had good results based on the Severin classification [14]. Castillo and Sherman similarly reported patients between 5 and 14 months old at the time of surgery had good results [1].…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction by the medial approach presents important advantages such as lesser tissue dissection, lower blood loss, cosmetically more favorable cutaneous incision, shorter surgical duration and bilateral applicability in an identical session. The most important disadvantages of this technique are inability to evaluate the pathological changes in the superior acetabulum and infeasibility of capsulography for stable reduction (1,2). In this study, we have evaluated the clinical and radiological outcomes, presence of potential complications such as avascular necrosis and also need to an additional surgery in the patients who underwent open reduction by the medial approach for DDH in our clinic.…”
Section: Introductionmentioning
confidence: 99%